WACANA EKOLOGI SOSIAL DALAM NOVEL PAK TUA YANG MEMBACA KISAH CINTA KARYA LUIS SEPÚLVEDA - Pramesti, I Gusti Ayu Diah; Amanda Gelgel, Ni Made Ras; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium; Vol 1 No 2 (2021): Jurnal Ilmu Komunikasi 2021, 2020)
ABSTRACT This research analyzed the presence of social ecology discourse in Pak Tua yang Membaca Kisah Cinta novel by Luis Sepúlveda through Norman Fairclough’s critical discourse analysis model. In textual analysis, the researcher found social ecology discourse in novel which included the ecological crises due to dominance of the state and capital; and ecological oriented culture of indigenous people. Based on discursive practice analysis, the presence of those discourse come from social cognition of Luis Sepúlveda who has believed in indigenous people’s ecological oriented culture, same as the publisher of this novel. Meanwhile, sociocultural practice analysis has shown the link between social and ecological problems in the novel with the history of discrimination against indigenous people and their resistance in Ecuador. Therefore, these three dimensions found that this novel with its social ecology idea has provided alternative perspective to supported a counter-discourse which indigenous people built to maintain ecology sustainability. Keywords : Critical Discourse Analysis, Social Ecology, Latin American Literature, Indigenous People of Latin Amerika